Aviation: the politics and economics of a boom. - Juan, Ellis J. (Foreign Policy)
The development of a single, integrated, international air-transport network is discussed. As the aviation industry grew in the 1950s and 1960s, governments started to regulate air transport heavily, citing national sovereignty and the need to maintain and defend airspace. Subsequently, deregulation of the domestic American airline market in 1978 and the “Open Skies” agreements on international air travel have stimulated enormous growth in international trade, tourism, and cross-border investment during the past decade. Any solution to the regulatory challenges posed by the globalization of the air-transport industry must start with those involved recognizing that airline consolidation is inevitable.